Penjualan Online dalam Perspektif Syariah - Ya'qub, Mohammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2023)
This article aims to investigate online retail transactions through the lens of Islamic Sharia law. Utilizing a library-based research approach, this study specifically examines the phenomenon of tiktok online shop. One of the key findings is that such online transactions frequently manifest elements of